Kontribusi Nilai-Nilai Islam dalam Peningkatan Hasil Pertanian di Kabupaten Pinrang: Contribution Islamic Values in Increasing Agricultural Yields in Pinrang Regency - Nurhasibah (IAIN Parepare, 2025)
The effectiveness of P3A in practice is often hampered by various obstacles. One of them is the low level of member participation in organisational activities. The study focuses on the role of Islamic values in irrigation management by the Mamminasae V P3A group in Padaelo Village, Pinrang Regency. Islamic values play a crucial role in strengthening cooperation and the effectiveness of water resource management, which is the main pillar supporting community agricultural activities. The application of Islamic principles not only strengthens social bonds but also promotes the creation of a fair, transparent, and sustainable irrigation system. This study uses a qualitative approach with a descriptive method to analyse the forms of Islamic values applied in P3A activities, the factors that strengthen or hinder their application, and strategies that can support the sustainability of irrigation systems based on spiritual and social values. Data collection techniques include in-depth interviews, observations, and document.studies. The results of the study indicate that the application of Islamic values in the Mamminasae V P3A group in Padaelo Village, Pinrang District, is reflected through thammana & ihtarama, tawāsūh, al-nazāhah & al-infitāh, mas'uliyyah, and al-'adl.in irrigation management. These values strengthen coperation in maintaining water channels, making fair decisions, and distributing water equitably according to mutual agreements. The tradition of mappalili, the attitude of tawakal, gratitude, and mutual assistance strengthen spiritual awareness and social solidarity among members. The application of these values significantly contributes to improving agricultural yields through social and spiritual principles.